Fractures of the Second Cervical Vertebra in 66 Dogs and 3 Cats: A Retrospective Study - Schmidli, Fenella E.; Stein, Veronika M.; Aikawa, Takeshi; Boudrieau, Randy J.; Jeandel, Aurelien; Jeffery, Nicholas; Jurina, Konrad; Moissonnier, Pierre; Rupp, Stefan; Vidondo, Beatriz; Forterre, Franck (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Background In human medicine, fractures of the second cervical vertebra have been studied elaborately and categorized in detail. This is not the case in veterinary medicine where clinical decisions are often based on old studies focusing on the cervical spine in general.Objectives The aim of this study was to describe the clinical features, fracture types, therapeutic options and outcome of dogs and cats with a fractured axis.Study Design The present study was a multi-institutional retrospective case series.Results Crossbreeds and Labrador Retrievers were the most represented dog breeds. Median age was 2 years. Motor vehicle accident was the most common inciting cause, followed by frontal collision. The most common neurological deficits ranged from cervical pain with or without mild ataxia (22/68) to tetraparesis (28/68) and tetraplegia (11/68). Concerning treatment, 37 of 69 patients underwent surgical fracture stabilization, 27/69 received conservative therapy and 5/69 were immediately euthanatized. Of all treated cases, 52/58 showed ambulatory recovery (23/25 of the conservatively treated and 29/33 of the surgically treated cases), whereby in 40/52 cases full recovery without persisting signs was achieved.Conclusions Fractures of the axis commonly occur in young dogs. In many cases, neurological deficits are relatively mild. Generally, animals with a fractured axis have a very good prognosis for functional recovery. The risk of perioperative mortality is considerably lower than previously reported.
Keywords: axis fractures; cervical fractures; fracture stabilization; dog; cat